Strangers to the Constitution : immigrants, borders, and fundamental Law. - Neuman, Gerald L. (Princeton University Press, 2001)
Gerald Neuman discusses in historical and contemporary terms the repeated efforts of U.S. insiders to claim the Constitution as their exclusive property and to deny constitutional rights to aliens and immigrants--and even citizens if they are outside the nation's borders. Tracing such efforts from the debates over the Alien and Sedition Acts in 1798 to present-day controversies about illegal aliens and their children, the author argues that no human being subject to the governance of the United States should be a "stranger to the Constitution."Thus, whenever the government asserts its power to